2016
DOI: 10.1186/s13075-016-0998-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A deficiency promotes periosteal bone formation in a model of inflammatory arthritis

Abstract: BackgroundInterleukin-17A (IL-17A) plays a pathogenic role in several rheumatic diseases including spondyloarthritis and, paradoxically, has been described to both promote and protect from bone formation. We therefore examined the effects of IL-17A on osteoblast differentiation in vitro and on periosteal bone formation in an in vivo model of inflammatory arthritis.MethodsK/BxN serum transfer arthritis was induced in IL-17A-deficient and wild-type mice. Clinical and histologic inflammation was assessed and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…Cytokines produced by Th17 cells can drive the differentiation of osteoclasts from precursors and these osteoclasts can tip the balance in the direction of bone resorption [29]. In addition to osteoclast increase, a recent study has shown that IL-17A can decrease osteoblast formation resulting in a net bone loss [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Cytokines produced by Th17 cells can drive the differentiation of osteoclasts from precursors and these osteoclasts can tip the balance in the direction of bone resorption [29]. In addition to osteoclast increase, a recent study has shown that IL-17A can decrease osteoblast formation resulting in a net bone loss [30]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, periosteal lamellar bone deposition occurs much more slowly, in agreement with a progression of melorheostotic lesions over years . Periosteal new bone formation is often viewed as a physiological response to focal insults or systemic condition such as infections, hemorrhages, inflammations (periostitis), osteonecrosis, tumor processes, and malign neoplasms such as Ewing's sarcoma or Caffey's disease . In fact, so‐called “periosteal reactions” occur widely and represent a rather nonspecific mechanism to maintain bone strength, counteracting the effects of cortical lysis or endocortical bone loss by forming a bridge over damaged cortical area .…”
Section: Discussionmentioning
confidence: 96%
“…We do not currently know the factors that drive the periosteal reaction in the melorheostosis lesion. It is, however, interesting that inflammation seems to act as a strong local stimulus . In that sense, it seems possible that inflammatory cytokines produced during overactive bone remodeling also trigger periosteal bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when inflammatory conditions are present, IL‐17A drives osteoclastogenic effects by disrupting the RANKL/RANK/OPG axis . It has been shown that IL‐17A deficiency resulted in increased periosteal bone formation in the K/BxN serum transfer model of inflammatory arthritis . This finding might seem contradictory to the IL‐17A–dependent increased bone regeneration in the drill‐hole injury animal model .…”
Section: Animal Models Showing a Role For Il‐23 In Enthesitismentioning
confidence: 99%